2015
DOI: 10.1055/s-0035-1545948
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Phytotherapy in Europe: Where Do We Stand?

Abstract: Medicinal plants represent the oldest source of pharmacotherapy used by mankind. A considerable number of traditional systems of medicine (folk medicine) have emerged over the last millennia under different cultural conditions. Even nowadays, the majority of people in less developed countries have to rely on herbal remedies as primary health care. Based on scientific and technical progress, the options to produce high quality herbal medicinal products have been largely improved in the last decades. The accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 12 publications
1
39
0
5
Order By: Relevance
“…This suggests that the A. argyi extract likely contains compounds affecting signaling on a more upstream target than the compounds isolated thus far. Our findings corroborate the notion of a multitarget effect of herbal extracts possibly resulting in pharmacological synergism (Fürst and Zündorf, 2015;Colalto, 2018). The study also demonstrates that the established cell-based screening platform approach is a powerful tool for identifying and characterizing potential immunosuppressive leads from natural product sources.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that the A. argyi extract likely contains compounds affecting signaling on a more upstream target than the compounds isolated thus far. Our findings corroborate the notion of a multitarget effect of herbal extracts possibly resulting in pharmacological synergism (Fürst and Zündorf, 2015;Colalto, 2018). The study also demonstrates that the established cell-based screening platform approach is a powerful tool for identifying and characterizing potential immunosuppressive leads from natural product sources.…”
Section: Discussionsupporting
confidence: 87%
“…For herbal medicinal products, traditional use may guarantee efficacy, but scientific data on safety and mechanisms of action useful to clinical practice (Claeson, ; Cravotto, Boffa, Genzini, & Garella, ; Turner, ) are available for very few medicinal plants. An interesting article by Fürst and Zündorf on “Evidence‐Based Phytotherapy in Europe” outlined the state of the art of herbal medicinal products, focusing on the quality and safety of these products, scientific evidence, and the regulatory system (Fürst & Zündorf, ). The authors gave a clear report and analysis of a number of problems arising here.…”
Section: Evidence‐based Medicine In the Case Of Phytotherapymentioning
confidence: 99%
“…The clinical investigation of plant extracts is often difficult in view of the high heterogeneity of the mixtures examined, but also as a result of bias regarding numbers of patients, duration of treatment, and other similar things. The authors concluded by outlining the strange discrepancy between the wide availability of these products and the frequently poor scientific information (Fürst & Zündorf, ). In a similar vein, the review of Izzo et al noted that a high number of systematic reviews had been published on the clinical efficacy of herbal extracts but warned that the reported evidence is often weakened by poor methodology and thus unreliable clinical analysis.…”
Section: Evidence‐based Medicine In the Case Of Phytotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The phytotherapeutics are standardized vegetable preparations that consist of a complex mixture of plant-based substances that are adequately prepared and prescribed in compliance with applicable legislation (Bettega et al 2011;Oliveira 2014, Fürst andZündorf 2015). Phytotherapeutic compounds, in general, can be used in a variety of formula such as capsules, tablets, gels, ointments, aqueous solutions, and infusions, such as tea (Francisco 2010).…”
Section: Introductionmentioning
confidence: 99%